Advances in research on spexin-mediated regulation of reproductive function in vertebrates - Chen, Xiaojing; Feng, Yuyan; Dai, Shudi; Guo, Binbin; Yan, Leyan; Liu, Jie; Zhu, Huanxi (Frontiers in Endocrinology, 2024)
Spexin (SPX, NPQ) is a 14-amino acid neuroactive peptide identified using bioinformatics. This amino acid sequence of the mature spexin peptide has been highly conserved during species evolution and is widely distributed in the central nervous system and peripheral tissues and organs. Therefore, spexin may play a role in various biological functions. Spexin, the cognate ligand for GALR2/3, acting as a neuromodulator or endocrine signaling factor, can inhibit reproductive performance. However, controversies and gaps in knowledge persist regarding spexin-mediated regulation of animal reproductive functions. This review focuses on the hypothalamicpituitary-gonadal axis and provides a comprehensive overview of the impact of spexin on reproduction. Through this review, we aim to enhance understanding and obtain indepth insights into the regulation of reproduction by spexin peptides, thereby providing a scientific basis for future investigations into the molecular mechanisms underlying the influence of spexin on reproductive function. Such investigations hold potential benefits for optimizing farming practices in livestock, poultry, and fish industries.